Advancements to treat various types of Male and Female Infertility - Sarwan, Jyoti; Pradhan, Nalini; Sridhar, Saranya; Singh, Alka; Rawat, Sakshi; Vashisht, Divyanshi; Kanishka, Kanishka; Sharma, Pallavi; Kaur, Dipneet (Journal of Neonatal Surgery, 2025)
Male infertility is a growing concern that affects approximately 15% of couples worldwide, with male factors contributing to nearly half of these cases. Recent studies have highlighted a significant relationship between obesity and male reproductive health, suggesting that excess body weight may negatively impact fertility through various biological mechanisms. Obesity is characterized by an increased accumulation of adipose tissue, which alters hormonal balance, particularly affecting testosterone levels and leading to metabolic dysfunction. Research indicates that obesity can lead to a state of chronic inflammation and oxidative stress, which can impair spermatogenesis and reduce sperm quality. Additionally, elevated body mass index (BMI) has been associated with lower sperm concentration, motility, and morphology. The mechanism behind these effects may include hormonal alternations, such as increased estrogen levels due to aromatization of testosterone in adipose tissue, as well as the detrimental impact of obesity –related comorbidities, including insulin resistance and diabetes. Endometriosis is a common estrogen-related disease in women of reproductive age, usually associated with chronic pelvic pain, infertility, and psychological distress, i.e., anxiety and depression. The condition is defined by the presence of endometrial glands and stroma implanted outside the uterine cavity, most typically found in the uterus, fallopian tubes, and ovaries. Pathophysiological processes include endocrine disturbances, immune derangement, and oxidative stress. Endometrial cells also secrete cytokines like MCP-1 and IL-6, which interfere with normal follicular development and luteal function. Sterility occurs in 30–50% of patients with endometriosis, creating management dilemmas and causing decreased quality of life. Diagnosis is largely dependent on non-invasive imaging studies, while therapy encompasses hormonal treatment, lifestyle changes, and ART like IVF. Surgical procedures have limited efficacy for established cases, and recurrence is frequent. New strategies such as high-intensity focused ultrasound (HIFU) and nanotechnology-based therapies hold great promise by treating lesions noninvasively and combating oxidative stress. Ethical dimensions of the treatment of endometriosis involve respecting patient autonomy, informed consent, and fair access to treatments. A multidisciplinary patient-centered model is necessary to maximize outcomes in endometriosis-associated infertility.